2015
DOI: 10.1002/etep.2150
|View full text |Cite
|
Sign up to set email alerts
|

A new ground impedance measuring element for digital distance relaying of long parallel lines in high fault resistance conditions

Abstract: SUMMARYGround impedance measuring elements (ground elements), which are responsible for removing singlephase-to-ground faults in distance relays, are highly prone to underreach when facing a significant resistance in the fault path. This paper proposes a new ground element with ensured dependability in high fault resistance conditions for the first-zone digital distance relaying of parallel lines. The proposed ground element functions on the basis of the fault distance and fault resistance it estimates, online… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…In the last decade, a vast number of research work have been reported on different aspects related to various faults in the area of underground power distribution system likely analysis of faults [25][26][27][28][29][30], adaptive fault [31][32][33], SC, OC and ground faults [34][35][36][37], detection [38,39], classification [40] and fault location [41][42][43][44][45][46], sustainable protection [47,48], noise monitoring [49], and for thermal test [50].…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, a vast number of research work have been reported on different aspects related to various faults in the area of underground power distribution system likely analysis of faults [25][26][27][28][29][30], adaptive fault [31][32][33], SC, OC and ground faults [34][35][36][37], detection [38,39], classification [40] and fault location [41][42][43][44][45][46], sustainable protection [47,48], noise monitoring [49], and for thermal test [50].…”
Section: Introductionmentioning
confidence: 99%
“…Transverse differential and distance schemes have been dominantly used for protection of double‐circuit lines. Distance schemes require zero‐sequence mutual compensation to correctly measure impedances in the case of ground faults 4 . Transverse differential schemes are faster in operation than conventional distance relays 5 but cannot be implemented unless circuit lines are in parallel 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Distance schemes require zero-sequence mutual compensation to correctly measure impedances in the case of ground faults. 4 Transverse differential schemes are faster in operation than conventional distance relays 5 but cannot be implemented unless circuit lines are in parallel. 6 The basic principle of transverse differential protection is based on differentiation between internal and external faults by using differential current amplitude and determination of faulted line by using differential current direction.…”
mentioning
confidence: 99%
“…13 The combined S-transform and logistic model tree techniques for fault classification and fault section identification in thyristor controlled series capacitor compensated transmission system have been reported in Moravej et al 14 In Pazoki et al, 15 the authors investigate the impact of a unified power flow controller on zones 1 and 2 (with infeed current) of the conventional distance relay and pilot protection schemes. The probabilistic neural network has been applied to detect and classify the power quality disturbance in Moravej et al 16 Further, the ground impedance element has been modified for protection of transmission line against high resistance fault in Abdollahzadeh et al 17 Support vector machines and hyperbolic S-transform has been used for fault detection, classification, and location estimation in SCCTL. 18 Recently, k-nearest neighbor-based fault detection, classification, and location estimation in SCCTL has been reported by authors.…”
mentioning
confidence: 99%